ТЕХНІКО-ЕКОНОМІЧНА ОЦІНКА ВИКОРИСТАННЯ СИСТЕМИ АКУМУЛЮВАННЯ ЕЛЕКТРОЕНЕРГІЇ ДЛЯ СТАБІЛІЗАЦІЇ РОБОТИ СОНЯЧНОЇ ЕЛЕКТРОСТАНЦІЇ - Буратинський, І.М. (Інститут електродинаміки НАН України, Київ, 2022)
The article considers the problems that arise during the operation of high-power photovoltaic solar power plants as part of integrated power systems. The necessity of using energy storage systems to stabilize the operation of solar power plants is described and the calculated mathematical model of their joint operation is given. A study of the operation of a solar power plant with a fixed capacity of photovoltaic modules of 20 MW together with the energy storage system and determined the capacity of batteries needed to stabilize the power supply of electricity to the grid. For the day with the largest volumes of electricity production, in order to fully stabilize the operation of a solar power plant, it is necessary to release 41% of all generated electricity directly into the grid, and other volumes must be accumulated with subsequent discharge. Connecting batteries to a solar power plant allows to reduce the installed capacity of inverters from 18 to 3-5 MW, which reduces the cost of electricity production by 13-16%. According to the data on capital investment and operating costs during the entire period of operation solar power plants together with the energy storage system for the built in 2020 and 2040, the levelized cost of energy, storage and supply into the grid was determined. References 12, figures 5, table 1.